Answer :

For finding zeroes, we’ll use the hit and trial method.

For that we’ll put a value which will make our polynomial zero.

Since, here the whole equation is combination of positive and negative that means, zero can be achieved by putting the positive or negative values.

So, first we’ll put x = 1.

⇒ (1)^{3} – 23(1)^{2} + 142(1) – 120 = 1 – 23 + 142 – 120

= 0

⇒ x = 1 is one of the zeroes.

Now, we’ll write the equation in terms of (x – 1) to make equation quadratic and hence to find the other zeroes.

⇒ x^{3} – 23x^{2} + 142x – 120 = x^{2} (x – 1) – 22x(x – 1) + 120(x – 1)

= (x – 1)(x^{2} – 22x + 120)

Now, using factorization by splitting the middle term method -

= (x – 1)(x^{2} – (12 + 10)x + 120)

= (x – 1)(x^{2} – 12x – 10x + 120)

= (x – 1)(x(x – 12) – 10(x – 12))

= (x – 1)(x – 10)(x – 12)

Now, to get the zeroes we’ll put these equals to zero.

⇒ x – 1 = 0, x – 10 = 0, x – 12 = 0

⇒ x = 1, x = 10, x = 12 are the zeroes of x^{3} – 23x^{2} + 142x – 120

Rate this question :